2017
DOI: 10.1159/000457132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Pleural Effusion in Patients with Pulmonary Embolism

Abstract: Background: Data regarding pleural effusion due to pulmonary embolism (PE) are limited. Objectives: The aim of this study was to investigate the clinical characteristics of PE patients with pleural effusion caused by PE. Methods: Patients with PE were retrospectively analyzed and divided into 2 groups based on computed tomography: a group with pleural effusion due to PE (effusion group) and a group without pleural effusion (control group). Clinical characteristics were compared between the 2 groups. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
3
20
1
2
Order By: Relevance
“…In agreement with the characterization of PI by Revel et al ., we found that PIs commonly demonstrated central lucency, were semicircular in shape, without air bronchograms, and were frequently associated with a feeding vessel . An ipsilateral pleural effusion was also significantly more frequent in patients with PI, an association that remained significant on multivariate analysis . PCP was also an independent predictor for PI.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In agreement with the characterization of PI by Revel et al ., we found that PIs commonly demonstrated central lucency, were semicircular in shape, without air bronchograms, and were frequently associated with a feeding vessel . An ipsilateral pleural effusion was also significantly more frequent in patients with PI, an association that remained significant on multivariate analysis . PCP was also an independent predictor for PI.…”
Section: Discussionmentioning
confidence: 50%
“…PIs were lower lobe predominant—a phenomenon observed in multiple other reports . An understanding of the physiology of pulmonary blood flow offers insight into this phenomenon.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recently published retrospective cohort studies have addressed the prognostic impact of pleural effusion in patients with PE. [9][10][11] This study shows that comorbidities play a key role in the development of pleural effusion in many patients with acute PE. Thus, discussion on pleural effusion as prognostic factor should address underlying comorbidities.…”
Section: Discussionmentioning
confidence: 66%
“…7,8 However, recent retrospective studies that addressed the prognostic impact of pleural effusion in cohorts of patients with acute PE have reported contradictory results. [9][10][11] It is not uncommon to observe bilateral pleural effusion (BPE) on CTPA scans of patients with acute PE. The clinical relevance of bilateral effusion may differ from that of unilateral effusion.…”
Section: Introductionmentioning
confidence: 99%